Psychological variables implied in the therapeutic effect of ayahuasca: A contextual approach. (June 2018) - Franquesa, Alba; Sainz-Cort, Alberto; Gandy, Sam; Soler, Joaquim; Alcázar-Córcoles, Miguel Ángel; Bouso, José Carlos
Highlights: Ayahuasca is being used for religious, therapeutic and personal growth purposes. The ayahuasca-induced introspective experience has been shown to have therapeutic potential. Contextual psychotherapy variables could explain the therapeutic effects of ayahuasca. Results confirm that ayahuasca users scored high in Decentering and Positive self. Scores in Decentering were higher in the more experienced subjects. Abstract: Ayahuasca is a psychedelic decoction originating from Amazonia. The ayahuasca-induced introspective experience has been shown to have potential benefits in the treatment of several pathologies, to protect mental health and to improve neuropsychological functions and creativity, and boost mindfulness. The underlying psychological processes related to the use of ayahuasca in a psychotherapeutic context are not yet well described in the scientific literature, but there is some evidence to suggest that psychological variables described in psychotherapies could be useful in explaining the therapeutic effects of the brew. In this study we explore the link between ayahuasca use and Decentering, Values and Self, comparing subjects without experience of ayahuasca ( n  = 41) with subjects with experience ( n  = 81). Results confirm that ayahuasca users scored higher than non-users in Decentering and Positive self, but not in Valued living, Life fulfillment, Self in social relations, Self in close relations and General self. Scores in Decentering were higher in the more experienced subjects (more than 15 occasions) than in those with less experience (less than 15 occasions). Our results show that psychological process variables may explain the outcomes in ayahuasca psychotherapy. The introduction of these variables is warranted in future ayahuasca therapeutic studies.